The Evolusi pendidikan islam: menyongsong masa depan dengan pondasi aqidah yang kuat - Nabilah, Nur Rahma (Maliki Interdisciplinary Journal, 2025)
Islamic education in the modern era faces great challenges due to technological developments, globalization and rapid social change. This article discusses the evolution of Islamic education which needs to adapt to changing times while still adhering to the strong principles of aqidah as a moral and spiritual foundation. Islamic education does not only focus on teaching religious texts, but also integrates aqidah values ​​which are able to shape the character and behavior of the younger generation. In facing the digital era, Islamic education must be able to balance the use of modern technology and teaching based on revelation, with the aim of developing individuals who are intellectually intelligent and strong in faith and morals. This article also discusses the importance of Islamic-based intracurricular and extracurricular activities in shaping student character, as well as the challenges of technological infrastructure and conservative organizational culture in Islamic educational institutions. Overall, the evolution of Islamic education that is responsive to current developments and remains faithful to religious principles is the key to facing the future with a generation that is ready to face global challenges without losing religious identity. The application of technology in learning, even though it has challenges related to infrastructure and resistance to innovation, is an aspect that needs to be integrated to support an educational process that is more responsive to current developments. With the right strategy in education management, strengthening Islamic values ​​in the curriculum, and improving technological skills for teaching staff, Islamic education can prepare future generations who are intelligent and have noble character in the digital era.